Analisis Peran Teknologi SITEK Reborn dalam Meningkatkan Efisiensi dan Intensitas Pengiriman Kargo Harian di PT. Integrasi Aviasi Solusi Regional 3 Surabaya - Hesti Meydawati; Rosiana Ulfa (Jurnal Manajemen Dirgantara, 2026)
This research is motivated by a significant increase in the volume of air cargo shipments in recent years demanding a more efficient and integrated management system, thus posing serious challenges in operational efficiency and data accuracy. PT Integrasi Aviasi Solusi Regional 3 Surabaya as a company that carries the concept of operational digitalization through SITEK Reborn, needs to evaluate the extent to which the application of digital transformation principles has been implemented, especially in managing cargo information systems and increasing operational efficiency. This research uses descriptive qualitative methods, with data collection techniques through observation, interviews and documentation. The research was conducted in May 2025 at PT Integration Aviation Solution Regional 3 Surabaya. Primary data sources were obtained from three resource persons responsible for operating the SITEK Reborn system at PT Integrasi Aviasi Solusi Regional 3 Surabaya. The results showed that the implementation of SITEK Reborn at PT Integrasi Aviasi Solusi Regional 3 Surabaya has successfully achieved a comprehensive digital transformation in daily cargo operations through the replacement of the G2 manual system with barcode scanning technology which resulted in a tremendous increase in operational efficiency, where data input time was reduced from 3-5 minutes to 5-10 seconds with time efficiency of up to 95%, throughput capacity increased from 150-200 AWB to 350-400 AWB per day, error rate dropped from 12-15% to less than 1%, inventory management accuracy increased from 88% to 99.5%, and better customer experience with reduced waiting time from 30-45 minutes to 5-10 minutes and reduced customer complaints by 80%. Despite facing multidimensional challenges of human resource constraints, technical infrastructure, regulatory complexity, and system scalability, the successful implementation was achieved through a holistic strategy that integrated phased training and mentoring programs, comprehensive IT infrastructure updates, flexible regulatory system adaptation, and scalable cloud architecture, thus proving that successful digital transformation requires an integrated approach between human resource development, technology modernization, regulatory compliance, and long-term capacity planning to create a sustainable and effective system to support business operations.